Book review: Vasanth Kannabiran, Taken at the Flood: A Memoir of a Political Life. (December 2020) - Patel, Vibhuti
Vasanth Kannabiran, Taken at the Flood: A Memoir of a Political Life . Delhi: Women Unlimited, 2020, vi + pp., 174, ₹375, ISBN 978-93-85606-26-7 (Paperback) .